Borneo Black Orchid Symbolism: Cultural and Islamic Intersections for Global Insights - Elmansyah, Elmansyah; Hasmy, Ali; Martina, Martina; Thoharudin, Munawar; Ekawati, Erna (Jurnal Ilmiah Peuradeun, 2025)
The Bornean Black Orchid is a rare and unique plant that grows exclusively in Kalimantan. However, no scientist or practitioner has yet attempted to explore its potential as a symbol of identity for organizations, social institutions, or government entities. This research aims to uncover the potential of the Bornean Black Orchid as an inspiration for the development of Islamic higher education with global benefits. The study employs a qualitative method with a philosophical approach, examining the existence of the Bornean Black Orchid and its relevance to a model for developing educational materials in higher education. Data were collected through direct observation at Selimbau Orchid Park and in-depth interviews with managers and the local community. The symbols derived from the orchid are interpreted philosophically to inform a higher education development model that integrates Islamic principles with Bornean culture. Contributions from experts and practitioners were gathered through a Focus Group Discussion (FGD). The research findings are as follows: 1) The Bornean Black Orchid is not only rare and unique but also embodies the original identity of the people of Kalimantan, reflecting superior characteristics; 2) The patterns of the Bornean Black Orchid can serve as a model for developing educational materials in higher education; 3) The characteristics of the Bornean Black Orchid can inspire the establishment of an Islamic university that is both exceptional and globally impactful.